Влияние света и температуры на интенсивность поглощения кислорода куколками непарного шелкопряда - Киреева-Золотоверхая, И. М. (Вестник зоологии, 1967)
The article deals with the problems of photothermal condition effect on the intensity of oxygen absorption by pupae of Porthetria dispar L. The author studies the effect of light in four variants: twenty-four-hour darkness, light during 7 hours, light during 17 hours and twenty-four-hour light. The experiments were conducted at the temperature of 16, 25, 28 and 32P C. Oxygen absorption was studied during the whole pupa stage. As a result of these investigations it is determined, that the curve showing the quantity of oxygen, absorbed by the pupae of Porthetria dispar L. independingly on photothermal conditions has a typical V-shaped form. Both increase of temperature and increase of duration of light caused the shortening of duration of pupa development and increase of intensity of oxygen absorption. The temperature is the principal factor during the simultaneous effect of temperature and light on pupa interchange of gases. The effect of photoperiodic factor is displayed the most distinctly at the low temperature.